Design and performance test of multi intake foods product cutting machine - Mizar, Muhammad Alfian; Nasir, Mohd Zakaria Mohammad; Trifiananto, Muhammad; Hardiatama, Intan (2023)
Appropriate technology is one of the answers to support small and medium enterprises in the sustainability of their business production. This research aims to design and test the performance of multi-intake food product cutting machines, this cutting machine can be applied to cutting food products such as tempeh, crackers, fruits, or tubers. This machine is called multi intake because it can cut more than one material at the same time and produce more cuts in a relatively short time. This machine is equipped with an automatic propulsion system that can produce pieces of uniform thickness. The results showed that the construction of a multiintake cutting machine for cutting food ingredients in the form of tempeh has a capacity of 120 kg h-1 to 173.5 kg h-1, the most optimal performance of the cutting machine for foodstuffs and can increase the capacity and quality of the stripping results achieved in the use of an electric motor with power 375 Watt with engine shaft rotation (n) = 327 rad s-1 and a thrust speed of 0.370 cm s-1 which can produce a cutting capacity of 173.5 kg h-1 with intact, not defective, and flat cut quality.